Kontribusi Kedisiplinan Belajar Dan Pola Asuh Orang Tua Terhadap Prestasi Belajar Siswa Kelas Tinggi SDN 02 Alastuwo Tahun Ajaran 2016/2017 - Rohmani, Tutut; , Drs. Saring Marsudi, SH. M.Pd (2017)
The purpose of this study (1) To describe the Contribution of Discipline Learning to Learning Outcomes. (2) To describe the Contribution of Parents Parenting Patterns to Learning Outcomes. (3) To describe the Discipline Contribution of Learning and Parenting Parenting to Learning Outcomes. This research includes the type of quantitative descriptive research with the conclusion through stasistik analysis. The study population of all high school students (IV, V, VI) SD Negeri 02 Alastuwo which amounted to 114 students. The sample consisted of 20 students of class IV, 16 students of class V, and 17 students class VI SD Negeri 02 Alastuwo. The sampling technique uses stratified random sampling. Data collection techniques used questionnaires and documentation. The technique of data analysis using multiple linear regression analysis, t test, F test, coefficient of determination, SR and SE which preceded by prerequisite analysis test that is normality test and linearity test. Based on the result of multiple linear regression analysis obtained equation: Y = 12,252 + 0,454X1 + 0,288X2. Results of data analysis 5% significance level obtained: (1) Discipline learning affects on learning achievement. This is based on t test result known that thitung> ttable, that is 3,923> 2,008 and significance value <0,05 is 0,023 with relative contribution equal to 61,9% and effective contribution equal to 22,6%. (2) Parenting patterns of parents affect the learning achievement. This is based on t test result known that thitung> ttable, that is 2,947> 2,008 and significance value <0,05, that is 0,005 with relative contribution equal to 38,1% and effective contribution equal to 13,9%. (3) Discipline learning and Parenting parenting effect on learning achievement. It is based on F test known that Fcount> Ftable is 14,349> 3,18 and its significance value <0,05, that is 0,002.